Analysis of harsh parenting practices: An islamic and psychological perspective - Dimas Fahrudin; Rofichatus Solihah; Riska Dwi Agustina; Triana Hermawati; Kana Safrina Rouzi; Azlan Shaiful Baharum (Yayasan Azhar Amanaa Yogyakarta, 2025)
The education process in childhood is one of the important prhase in the human’s growth and character development. This education process is usually conducted by parents as the main educators and also by teachers as educators in school institutions. Children who receive a good education will usually grow up with good behavior, while children who receive bad education will usually produce bad behavior. One of the bad methods in educating children is violent education. Starting from verbal violence in the form of insults, ridicule, gaslighting, belittling, to physical violence. The cause of violence behavior from educators (parents or teachers) to children can be many things, such as culture, psychological conditions of educators, or lack of insight and awareness from educators. According to psychology experts, violence behavior in educating children will actually have a negative impact on the child's mental condition and academic achievement. Not much different, Islamic scholars also warn of the dangers of being violent in educating children, because it will actually produce children with bad characters and traits while the goal of education may not archieved